Khāo kl̨ōn s̨ō Chīangtung = Chiengtung poems - Peltier, Anatole-Roger (Rombaibun Sangkhaphan, 1994)
Thai transcription of Khün epic narrative-poems from Shan States of Burma on pilgrimage of Phra Chao Rakheng, worshipping Buddha image, observance of Five Precepts, etc.